Biodegradation study of I lignin-based rigid polyrethane foams - Lopretti, M. (2012)
Polyurethanes are considered as one of the most versatile polymeric materials offering a wide range of products with applications in diverse sectors. Rigid polyurethane (RPU) foams belong to this class of products and represent a commercially important class of expanded materials. In the present work RPU foams have been prepared from lignin-based polyols (LP) obtained by oxypropylation of two technical lignins (Alcell and Indulin AT) and biodegradability evaluated using respirometry tests in liquid and solid media. A RPU foam produced from a commercial polyether polyol (CP) based on sorbitol (Lupranol® 3323) was used as reference. Lignin biodegradation by P. chrysogenum, T. harzianum, T. reesei, T. versicolor and P. chrysosporium fungi was tested. Respirometry tests (in liquid and solid media) were performed and foam’s biodegradation evaluated based on the produced CO2.